Tracking missed opportunities for an early HIV diagnosis in a population of people living with HIV with known time of infection. (19th February 2021) - Basoulis, Dimitrios; Kostaki, Evangelia Georgia; Paraskevis, Dimitrios; Hatzakis, Angelos; Psichogiou, Mina
Abstract : Purpose: The goal of 90-90-90 first requires the expansion of access to HIV testing. Our aim was to record frequencies of HIV indicator conditions (ICs) and identify missed opportunities for an early HIV diagnosis. Methods: We retrospectively identified ICs in a population of 231 people living with HIV with known infection dates who attended our clinic. The study population was divided into four groups: (1) those self-tested pre-emptively (47/231, 20.3%), (2) those offered targeted testing based on risk factors (67/231, 29%), (3) those tested after an IC (73/231, 31.6%) and (4) those who were not offered testing after an IC (44/231, 19%). HIV acquisition dates were estimated by molecular clock analysis. Results: A total of 169 healthcare contacts (HCCs) were recorded. The most frequent HCC was mononucleosis-like syndrome (20.1%), unexplained weight loss (10.7%) and STIs (10.1%). AIDS-defining conditions were detected in 11.8%. Only 62.4% (73/117) of those with an IC were offered testing after their first HCC. Patients in group 4 had statistically significant delay in diagnosis compared with group 3 (109.1 weeks (IQR 56.4–238.6) vs 71.6 weeks (IQR 32.3–124.6)). The proportion of patients diagnosed as late presenters in each group was: (1) 16/47 (34%), (2) 37/67 (55.2%), (3) 43/73 (58.9%) and (4) 27/44 (61.4%) (p=0.027). Conclusions: Our study uses a combination of molecular and clinical data and shows evidence that late presentation occurs in a high proportion of patients even in the presence of an IC. Given that risk-based targeted testing has low coverage, IC-guided testing provides a reasonable alternative to facilitate earlier HIV diagnosis and to improve late diagnosis across Europe and globally.